HUBUNGAN KECEMASAN TERHADAP PARTISIPASI PEMERIKSAAN IVA PADA WANITA USIA SUBUR (WUS) DI DESA SINAR BANTEN KECAMATAN BEKRI KABUPATEN LAMPUNG TENGAH TAHUN 2018 - Eka Tri Wulandari; Puji Lestari (Universitas Aisyah Pringsewu, 2020)
Breast cancer ranks first in all cancers in women (40 incidence rate per 100,000 women), new cases found 30.5% with 21.5% annual deaths from all cancer cases in women in the world. Cervical cancer ranks second with a incidence rate of 17 per 100,000 women, a new case found 13.0% with a death rate of 10.3% per year from all cancer cases in women in the world. (Ministry of Health, 2015). The results of the pre-survey achievement in Sinar Banten Village which carried out the IVA test in 2017 were 37 people or only 35.5%. yearly target of 104 people, this is due to WUS's anxiety to go to a health facility. The purpose of this study was to determine the Anxiety Relationship Against Participation in Iva Examination in Fertile Age Women in Sinar Banten Village Bekri District, Lampung Tengah Regency in 2018. This type of research is quantitative research, with a case control design. Population is the overall research subject (Arikunto, 2006). The population in this study were all WUS who conducted IVA examinations in Sinar Banten Village in 2018 as many as 37 people. The sample in this study were 37 people as a case and 37 people as controls in this analysis used the chi squar formula statistical test. Relationship of anxiety towards Participation in Examination IVA The results of the statistical tests obtained p value 0.018 (p value <a: 0.05), which means that there is a statistically significant relationship between anxiety and participation in IVA examination. , there are 60 (81%) respondents who experience anxiety, while 14 (19%) respondents who do not experience anxiety, it is expected that the health center can improve human resources related to IVA services and bring access to the target so that the program achievement is in accordance with what has been set.